The Ability of Patients With Schizophrenia to Comprehend and Produce Sincere, Deceitful, and Ironic Communicative Intentions: The Role of Theory of Mind and Executive Functions - Bosco, Francesca M.; Berardinelli, Laura; Parola, Alberto (Frontiers in Psychology, 2019)
Patients with schizophrenia are often described as impaired in several cognitive domains. Specifically, they often exhibit problems in solving tasks requiring theory of mind (ToM), i.e., the ability to ascribe mental states to oneself and to others, communicative-pragmatic ability, i.e., the ability to use language and non-verbal expressive means to convey meaning in a given context, and executive functions (EF). This study aims to investigate the role that cognitive functions, such as general intelligence, selective attention, processing speed, and especially EF (working memory, cognitive flexibility, inhibition, and planning) and ToM, play in explaining the ability of individuals with schizophrenia to comprehend and produce communicative acts expressed with different communicative intentions (sincere, deceitful, ironic) that are realized through linguistic and extralinguistic/non-verbal expressive means. Thirty-two patients with schizophrenia and an equal number of healthy controls were administered tasks aimed at investigating their ability to comprehend and produce sincere, deceitful and ironic communicative acts, in addition to a series of cognitive tasks evaluating EF and ToM. The results indicated that individuals with schizophrenia performed worse than controls in the comprehension and production of all the pragmatic phenomena investigated, as well as in all the cognitive functions examined. Patients with schizophrenia also exhibited an increasing trend of difficulty in comprehending and producing sincere, deceitful and ironic communicative acts, when expressed through either linguistic or extralinguistic means. Furthermore, a multiple regression analysis of the patients’ performance on pragmatic tasks revealed that, overall, the role of attention, general intelligence and processing speed did not appear to significantly explain the patients’ communicative-pragmatic performance. The inclusion of EF into the analysis did not contribute to increase the explained variance of the patients’ ability to comprehend and produce the various pragmatic phenomena investigated. Only the addition of ToM was able to significantly increase the explained variance, but only for the comprehension and production of deceit expressed by language, and the production of sincere communicative acts, also limited to linguistic production. We conclude that neither EF nor ToM are able to explain the decreasing trend we detected in patients’ pragmatic performance.